Caregiver, secondary victim: outcome of caring for patients with COVID -19: a qualitative content analysis study - Safieh Faghani; Fazlollah Ahmadi; Eesa Mohammadi (BMC, 2023)
Abstract Background Considering the importance of caring for patients with COVID -19 at home and the majority of care being the responsibility of family caregivers, it is necessary to identify and assess the problems during the implementation of patient care in family caregivers. Therefore, the present study was conducted to discover the different consequences of caring for patients with COVID-19 in family caregivers. Method Using Purposive sampling, 15 female family caregivers were included in the study. This study was conducted between 2021 and 2022 in Iran. Unstructured face-to-face and virtual interviews were used to collect data until data saturation was reached. Data were analyzed through Granheim and Lundman conventional content analysis approach. Results The analysis of data related to the outcome of caring for patients with COVID -19 in family caregivers, led to the extraction of six subcategories: " caregivers experiencing physical symptoms ", "perception of extra pressure and psychological symptoms in the caregiver", "disruption in marital relations", "feeling of homelessness and rejection" and " role pressure due to lack of family support". The subcategories led to the development of the main category "caregiver, the secondary victim", which is experienced by family caregivers during the provision of care for patients with COVID -19. Conclusion Family caregivers experience high levels of negative consequences from providing care to patients with COVID-19. Therefore, more attention should be paid to all dimensions of caregiver health such as physical, mental, and marital to provide quality care to patients finally.